BAGAIMANA KEDAI KOPI OHAYOU MENINGKATKAN PROSES KEPUTUSAN PEMBELIAN KONSUMEN DI KOTA BANDUNG - Sharon Cabrian (Business Administration Department - Universitas Katolik Parahyangan, 2021)
According to Toffin, in 2019 there was a 3-fold increase in the coffee shop business compared to the previous 3 years. An increase in the number of coffee shops is a threat and a challenge for coffee shop business owners. Ohayou Bandung is one coffee shop that is facing competition in the increasing number of coffee shops in the Ciumbuleuit area, Bandung. Due to its strategic location where UNPAR students are the target market, Ohayou has a great opportunity to meet the demand for coffee and public spaces. For this reason, companies need to pay attention to product attributes which are one of the main factors that are considered by consumers and customers in purchasing decisions. The purpose of this study was to determine whether product attributes and service quality affect purchasing decisions at Ohayou Bandung. Product attribute variables are measured by the dimensions of quality, features, design, brand, and packaging. Service quality variables are measured by the dimensions of reliability, responsiveness, assurance, empathy, and physical evidence. The variable of the purchasing decision making process is measured by the dimensions of problem recognition, information seeking, evaluation of alternatives, purchasing decisions, and post-purchase behavior. The results showed that the product attributes and service quality influenced purchasing decisions by 28.7%. In multiple linear analysis it is concluded that product attributes have a greater influence on purchasing decisions than service quality. Based on the partial hypothesis test, product attributes partially influence purchasing decisions. Meanwhile, service quality has no partial effect on purchasing decisions. It is concluded that improving service quality alone is not sufficient to improve purchasing decisions. Ohayou Bandung is advised to improve product quality and features, as well as increase the use of social media. Keywords: Product Attributes, Service Quality, Buying Decision, Ohayou Bandung